Should Agricultural Editors Assist Classroom Teachers? - William L. Carpenter (Journal of Applied Communications, 1970)
The Agricultural Editor's office is in a good position to move into the classroom, particularly with audio-visual skills. In a few states this is now being done, generally where there is no university-wide teaching resources center.